2010
DOI: 10.12989/scs.2010.10.5.429
|View full text |Cite
|
Sign up to set email alerts
|

Air blast load generation for simulating structural response

Abstract: The current research presents a detailed methodology for generating air blast loading for use within a finite element context. Parameters describing blast overpressure loading on a structure are drawn from open literature sources and incorporated within a blast load generation computer code developed for this research. This open literature approach lends transparency to the details of the blast load modeling, as compared with many commonly used approaches to blast load generation, for which the details are not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 15 publications
1
6
0
1
Order By: Relevance
“…This also suggests that for a shock strength exceeding 7 bar, the ideal gas EOS cannot be used. Here, it should be noted that this limit of applicability of the ideal gas EOS is in line with the suggestion of Brode [12] and Guzas & Earls [13]. However, model II can predict the maximum value of reflection coefficient to be approximately 10.…”
Section: (A) Comparison Of Different Modelssupporting
confidence: 88%
See 1 more Smart Citation
“…This also suggests that for a shock strength exceeding 7 bar, the ideal gas EOS cannot be used. Here, it should be noted that this limit of applicability of the ideal gas EOS is in line with the suggestion of Brode [12] and Guzas & Earls [13]. However, model II can predict the maximum value of reflection coefficient to be approximately 10.…”
Section: (A) Comparison Of Different Modelssupporting
confidence: 88%
“…Brode [12] reported that for a peak over-pressure higher than 6.9 atm, the reflection coefficient measured by the ideal gas EOS is increasingly in error and should not be used. Guzas & Earls [13] also restricted the application of ideal gas EOS to a peak over-pressure below 6.9 atm in their proposed methodology for calculating load on structures subjected to air blast. Baker [11] reported that non-ideal behaviour, such as dissociation and ionization of gases, is responsible for such high values of for the reflection coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…As it was mentioned before using the incident impulse diagram causes a change in the TNT equivalency factor, which is used for calculating 𝑘 𝑟𝑒𝑓 . In this way it is obtained as 𝑘 𝑟𝑒𝑓 = ( 𝑊 𝑇𝑁𝑇−𝑒𝑞 𝑊 𝑚𝑎𝑡 ) 1 3 ⁄ [28]. In table 6 𝑘 = 𝐶𝑎𝑙_𝐼 𝑠𝑜 /𝑊 1/3 𝐼 𝑠𝑜 /𝑊 1/3 that it was discussed above.…”
Section: Validationmentioning
confidence: 98%
“…Another widely used quantity to measure a blast's intensity, damage potential and energy is its impulse per crossectional area (Schnurr et al, 2020;Guzas & Earls, 2010;Kinney & Graham, 1985;Bush et al, 1946), which can be obtained as the time integral of the initial positive pressure peak of a microphone pressure curve as…”
Section: Radial Dependency Of Airborne Blast Pulsementioning
confidence: 99%